2004
DOI: 10.1021/ja031627v
|View full text |Cite
|
Sign up to set email alerts
|

Ellipsometric Approach for the Real-Time Detection of Label-Free Protein Adsorption by Second Harmonic Generation

Abstract: Second harmonic generation (SHG) was performed using a novel ellipsometric detection approach to selectively probe the real-time surface binding kinetics of an unlabeled protein. The coherence of nonlinear optical processes introduces new possibilities for exploiting polarization that are unavailable with incoherent methods, such as absorbance and fluorescence. Adsorption of bovine serum albumin (BSA) at silica/aqueous solution interfaces resulted in changes in the polarization state of the frequency-doubled l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 49 publications
1
42
0
Order By: Relevance
“…72 SHG-CD was shown to be a particularly sensitive probe of the redox state of the heme group, which is known to be essential for the electron transfer process that occurs in cytochrome c. Simpson and co-workers used chiral SHG experiments to observe the dynamics of protein binding (bovine serum albumin) to a surface. 73 Their experimental results are shown in Figure 7. Recently, chiral SHG signals from the peptide melittin allowed Conboy et al to detect its binding to a lipid bilayer.…”
Section: Surface Nonlinear Opticsmentioning
confidence: 99%
“…72 SHG-CD was shown to be a particularly sensitive probe of the redox state of the heme group, which is known to be essential for the electron transfer process that occurs in cytochrome c. Simpson and co-workers used chiral SHG experiments to observe the dynamics of protein binding (bovine serum albumin) to a surface. 73 Their experimental results are shown in Figure 7. Recently, chiral SHG signals from the peptide melittin allowed Conboy et al to detect its binding to a lipid bilayer.…”
Section: Surface Nonlinear Opticsmentioning
confidence: 99%
“…[97] In other studies, Polizzi et al have developed an ellipsometric approach for selectively probing the orientational changes induced within a weakly bound SHG-active local probe molecule upon coadsorption of a protein. [33] In general, any perturbation that significantly changes the nonlinear optical properties of an interface can be selectively isolated simply by placing an appropriately oriented combination of a quarter-wave plate and half-wave plate in the path of the detected nonlinear optical beam. [33] In one specific example of this general approach, bovine serum albumin (BSA) binding at the glass/aqueous solution interface was measured in real time and with chiral specificity by the structural chirality induced in an achiral rhodamine dye coadsorbate ( Figure 5) upon protein binding.…”
Section: Chirality In Nonlinear Optical Biosensing Applicationsmentioning
confidence: 99%
“…[1,4,5, The chiral specificity of these methods also opens up new opportunities for the development of chiral-selective surface detection and analysis approaches. [32,33] Emerging second-harmonic and sum-frequency microscopy methods for imaging biological samples demand an understanding of the role of chirality to assist in interpreting the nonlinear optical image contrast. [34][35][36][37][38][39][40][41] Additionally, the novel symmetry properties of SHG and SFG in chiral media suggest that new nonlinear optical materials can be constructed that exploit these chiroptical effects.…”
Section: Introductionmentioning
confidence: 99%
“…Electronic resonance enhancement is used to detect chiral SFG vibrational spectra generated from the molecular chirality, because under electronic resonance the asymmetric Raman tensor components will be greatly enhanced by the electronicvibrational coupling (18). Strong SHG and SFG signals can be observed from chiral molecules; however, Simpson and coworkers (33)(34)(35)(36)(37) demonstrated by using SHG that achiral molecules adsorbed on a surface or interface may generate detectable nonlinear optical chiral signals. They concluded that macromolecular orientational effects can dominate the chiroptical responses of uniaxial systems.…”
mentioning
confidence: 99%